Optimization of Social Media Based on Information and Communication Technology in Population and Civil Registration Office of Surabaya - Rio Febriannur Rachman (2022)
This study describes the implementation of public policies on the use of information and communication technology. This qualitative study applies a virtual ethnographic approach. The analysis is carried out by observing website and media pages at four levels; space, document, object, and experimental. The results of this study indicate that the Population and Civil Registration Office of Surabaya has optimized the official website, Twitter, Instagram, and YouTube. Optimization of social media gives convenience for all citizens from various backgrounds to access public services. This policy reduces the use of paper which means it is environmentally friendly. Utilization of media in the network makes services more transparent and accountable. All processes are neatly documented and monitored.